Constructing resilient systems in the historic south - Makenna Coon; Kindall Brantley (Urban Food Systems Symposium, 2020)
The College of Charleston (C of C) is a South Carolina Liberal Arts College that prides itself on giving students a far-‐reaching, multi-‐disciplinary education. Developing a Restorative Agriculture Program in this environment has proven to fall within C of C’s stated appreciation for diverse learning. The Restorative Agriculture Program tackles issues of urban food production by practicing space-‐intensive methods including companion planting, forest gardening, guilds, crop rotation, and intensive hot composting to utilize limited space for efficient production. This high intensity practice demands that resources are used in a strategic manner where nothing is wasted. With our gardens on campus, we demonstrate to the community and campus the many ways to alleviate waste while offering a location to do so, exemplified by the compost drop off we offer to campus. As a campus in a historic city, there are unique aesthetic and cultural guidelines we must adhere to. We have learned to use different protocols when educating others to create sustainable and creative communities. Similar to the plants we work with, we try to develop a network of support from different areas of the campus and community including various educational departments, the library, local horse stables, and surrounding stores and restaurants. Working with a variety of departments has built a synergistic arrangement where overlapping resources, knowledge bases, and support provide a larger opportunity to succeed. Currently the program is still in its beginning phases and the development to come will be fostered by current and future relationships in the Charleston community. As our knowledge widens with every experience, more opportunities develop to share this information to the larger community. Our program ultimately seeks to provide an alternative approach to learning about oneself, leadership, community, and active citizenry through restorative agriculture.
Keywords: restorative agriculture; alternative education; permaculture; tactical urbanism; regenerative project development; land tenure